EVALUATION OF COMPETENCES: METHODOLOGY AND TECHNOLOGIES (EXPERIENCE OF KURSK STATE MEDICAL UNIVERSITY) - Aleksandr I. Konoplya; Tatyana D. Vasilenko (Высшее образование в России)
The competence approach in the Russian educational sphere not only changes the goal paradigm and the content of education but demands revising the position of a higher educational institution and that of a student in the process of his professional acquisition. We have described the conceptual difficulties of the introduction of the competence approach into medical education and the ways of their solving at Kursk state medical university. The technologies and approaches to competence formation require methodological comprehension taking into account the specificity of the professional orientation and of the kinds of future professional activities of a graduate. The experience of Kursk state medical university is based on a competence model of student’s efficient professional activities in multiHcasual conditions specific for the activities of a medical worker in modern conditions. The article dwells on the methodological principles of implementing the competence approach at medical higher school providing both the formation processes and the procedures of evaluating the competence quality.